Deixe seu carro em casa: o efeito da consciência ecológica e do framing de perda e ganho em campanhas de marketing social - Galvão, Reny Aparecida (2013)
Researches on the effect of Ecological Consciousness in consumer behavior is still incipient in Brazil and , combined with the use of framing of gain and loss in advertising social marketing , are rarer still. In this perspective, the objective of this research was to analyze the effect of ecological awareness and the framing of loss and gain in social marketing campaigns. To better understand this issue, first we performed a literature search and subsequent empirical research , which was conducted an experiment with two stimuli, one with loss framing and one with gain framing. The data obtained through the sample, consisting of 200 people who answered the survey through social networks Facebook and Linkedin, were compiled and analyzed by the procedure of analysis of variance , using the SPSS 15.0 software. Through the analysis of the results of the experiment it was concluded that the variable ecological awareness has great moderating effect on the intention of consumers to drive less. While the framing effect of loss has greater effect, only in low consumer awareness Ecological.